The application of the theory of Visitor Attractions and its impact on the competitive advantage of the Tourism Sector in Durban, South Africa - S., R Balkaran (Journal of Economics and Behavioral Studies, 2013)
Visitor attractions become the nexus in the relationship between the Tourism sector and the city of Durban as a competitive destination and are arguably the most significant component within the tourism system. To become competitive within the attraction sector there is a need to have a combination of attractions, like sightseeing, shopping, entertainment, gaming, culture and recreation and these plays an important role in determining the competitiveness of a destination. The increase in tourist activity creates an environment where all stakeholders within the tourism system have an opportunity to exercise their function in the most appropriate way. This however does not occur without challenges and clearly, from general observations, the Tourism sector is faced with several challenges in Durban such as the lack of synergy between the stakeholders within the tourism system; standards and quality between various groups differ which impact on service delivery, price structure and foreign expectations; sustaining a high cost capital and labour intensive industry throughout the year; domestic tourists having to compete with currency fluctuations; and the social, political, economic and technological challenges. The development of a competitive model would contribute to tourism sustainability, which is vital for the economy, growth and further development of the Tourism sector in Durban, South Africa.